2017
DOI: 10.3762/bjnano.8.141
|View full text |Cite
|
Sign up to set email alerts
|

Low uptake of silica nanoparticles in Caco-2 intestinal epithelial barriers

Abstract: Cellular barriers, such as the skin, the lung epithelium or the intestinal epithelium, constitute one of the first obstacles facing nanomedicines or other nanoparticles entering organisms. It is thus important to assess the capacity of nanoparticles to enter and transport across such barriers. In this work, Caco-2 intestinal epithelial cells were used as a well-established model for the intestinal barrier, and the uptake, trafficking and translocation of model silica nanoparticles of different sizes were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 53 publications
(75 reference statements)
1
31
0
Order By: Relevance
“…While the NH 2 -PS are a good example to study toxicity induced by positively charged materials, for the SiO 2 nanoparticles ambivalent toxic effects have been reported. In fact, silica nanoparticles are usually considered non-toxic (Bexiga et al 2011;Shapero et al 2011;Lesniak et al 2012;Wang et al 2013aWang et al , b, 2018Ye et al 2017). However, other investigations have demonstrated that SiO 2 nanoparticle exposure can hamper cellular functioning (Wiemann et al 2016;Mohamed et al 2011;Lankoff et al 2013;Kim et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the NH 2 -PS are a good example to study toxicity induced by positively charged materials, for the SiO 2 nanoparticles ambivalent toxic effects have been reported. In fact, silica nanoparticles are usually considered non-toxic (Bexiga et al 2011;Shapero et al 2011;Lesniak et al 2012;Wang et al 2013aWang et al , b, 2018Ye et al 2017). However, other investigations have demonstrated that SiO 2 nanoparticle exposure can hamper cellular functioning (Wiemann et al 2016;Mohamed et al 2011;Lankoff et al 2013;Kim et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unlike to scarcely available alveolar macrophages harvested from bronchoalveolar lavage, this robust system provides unrestricted amounts of primary macrophages for detailed biochemical analysis. Given these unique features, we selected MPI cells to characterize in detail the response of alveolar-like macrophages to two well-characterized nanoparticle types, for which extensive information on the effect on other cell models is already available in literature (Bexiga et al 2011;Shapero et al 2011;Lesniak et al 2012;Wang et al 2013aWang et al , 2018Ye et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it was reported that the undifferentiated Caco-2 cells are more prone than differentiated ones to internalize nanomaterials, such as graphene oxide, quantum dots, TiO 2 and SiO 2 nanoparticles. [21,[62][63][64] In particular, Kucki et al recently demonstrated that the very dense brush border (made of microvilli) of differentiated intestinal epithelium led to low adhesion of GO sheets and steric hindrance for material uptake. [21] However, a clear understanding of GRM internalization into the cells has not been achieved yet, due to the poor internalization and the difficulty to have comparable in vitro models.…”
Section: Cellular Uptake and Intracellular Localization Of Digested Grmsmentioning
confidence: 99%
“…Therefore, the well-established intestinal model of differentiated Caco-2 cells has been used (Fogh et al, 1977, Lampen et al, 2004. These cells can mimic the intestinal epithelium and so can be used for in vitro uptake experiments (Xia et al, 2017, Ye et al, 2017, Je et al, 2017. As an enhancement of the Caco-2 model, cocultures, which are simulating the intestinal mucus (Lesuffleur et al, 1990, Wen et al, 2013, Castiaux et al, 2016 and M-cells (Gullberg et al, 2000, des Rieux et al, 2007, Lichtenstein et al, 2015, have been established.…”
Section: Introductionmentioning
confidence: 99%